Visible-light-promoted degradation of the antioxidants propyl gallate and t-butylhydroquinone: Mechanistic aspects - Criado, Susana Noemi (2012)
The kinetic and mechanistic aspects of the visible-light-mediated photodegradation of the phenolic antioxidants (PA), propyl gallate (PG), and t-butylhydroquinone (TBHQ), employing riboflavin (Rf) as photosensitizer, have been studied by time-resolved and stationary techniques. The photosensitizer Rose Bengal (RB) was used for auxiliary experiments. Results show the occurrence of chemical transformations on PA with the participation of electronically excited states of Rf and different reactive oxygen species (ROS) generated from these states. With 0.02 mM Rf and 1.0 mM PA, the electronically excited triplet state of Rf is quenched by PA, in a competitive manner with the dissolved oxygen. As a consequence, a cascade of photoprocesses produces singlet oxygen (O2(1Δg)) and H2O2 in the case of PG and, O2(1Δg), H2O2 and HO. in the case of TBHQ. The participation of these species is supported by experiments of oxygen consumption carried out in the presence of specific ROS scavengers. TBHQ has a relatively high capacity for O2(1Δg) physical deactivation and a low photodegradation efficiency by the oxidative species. Comparatively, it can be asserted that TBHQ has a higher antioxidant capacity than PG.